Improving The Quality of Learning with The 5R Method of Housekeeping Management (Ringkas, Rapi, Resik, Rawat, Rajin) at SMKN 3 Bekasi City - Munandar; Annuri; Firdaus, Rizal (Proceeding International Conference on Education, 2023)
The results of the Program for International Student Assessment (PISA) survey published in March 2019 show that there are problems with the quality of Indonesian education. The research aims to understand the implementation, obstacles and future strategies for housekeeping management of the 5R method in order to improve the quality of learning at SMKN 3 Bekasi. The research was designed using a qualitative descriptive method with data sources from informants by means of interviews, observation and documentation. Data analysis procedures used reduction, display, and conclusion techniques by verifying the validity of the data through triangulation of sources and methods. The results showed that the 5S method of housekeeping management was inconsistent, not in accordance with the 12 stages of implementing industry standards. With obstacles in the form of no leadership commitment and no clear work program.